Quantitative Trait Loci Associated with Foliar Trigonelline Accumulation in Glycine Max L. Issue 3 (1st November 2002) - Cho, Youngkoo; Njiti, Victor N.; Chen, Xinbo; Triwatayakorn, Kanokporn; Kassem, My Abdelmajid; Meksem, Khalid; Lightfoot, David A.; Wood, Andrew J.
Abstract : The objective of this study was to utilize a Glycine max RIL population to (1) evaluate foliar trigonelline (TRG) content in field-grown soybean, (2) determine the heritability of TRG accumulation, and (3) identify DNA markers linked to quantitative trait loci (QTLs) conditioning variation in TRG accumulation. Frequency distributions of 70 recombinant inbred lines showed statistically no significant departure from normality( P > .05 ) for TRG accumulation measured at pod development stage (R4). Six different molecular linkage groups (LGs) (B2, C2, D2, G, J, and K) were identified to be linked to QTLs for foliar TRG accumulation. Two unique microsatellite markers (SSR) on two different linkage groups identified QTL significantly associated with foliar TRG accumulation: a region on LG J (Satt285)( P = .0019,   R 2 = 15.9% ) and a second region on LG C2 (Satt079)( P = .0029,   R 2 = 13.4% ) .